Improving Employee Performance: The Role of Engagement, Transfer, Compensation, and Motivation in Work Productivity - Lestari, Dwi Ayu; Deviastri, Lily (SAN Scientific, 2025)
The purpose of this study is to investigate how motivation, pay, transfers, and employee engagement affect worker performance. The study's population consisted of employees from the Jakarta Cakung Primary Tax Service Office, with a sample size of 89 respondents. A non-probability sampling method was employed, specifically utilizing saturated sampling through the dissemination of surveys. Significant appropriateness is demonstrated by the study model's substantial effect and high degree of relevance in result prediction. The Partial Least Square Structural Equation Modeling (PLS-SEM) approach was used to analyze the data. The results show that employee performance is positively and significantly impacted by employee engagement. Furthermore, motivation, pay, and transfers all have favorable and noteworthy influence on performance. According to the research's management implications, managers need to create a welcoming workplace that encourages employee involvement, including offering career development opportunities. Moreover, it is essential for managers to provide necessary support through additional training and adequate orientation, while also encouraging employees to actively participate in training programs and enhancing their skill sets.